Medial meniscal root tears and meniscal extrusion transverse length ratios on MRI - Park, H-J (The British Institute of Radiology., 2012)
OBJECTIVE: To evaluate the clinical utility of the meniscal extrusion transverse ratio of the medial meniscus in the diagnosis of meniscal root tear compared with the gold standard of arthroscopic diagnosis. METHODS: This retrospective study sample included 32 males and 35 females who underwent MRI at our institution. There were 24 meniscal root tear cases. The control groups were 18 cases of medial meniscal tears without root tears and 25 cases of negative meniscal findings on arthroscopy. Meniscal extrusion (L) and maximal transverse lengths (T) of the medial meniscus were measured, and L/T ratios were calculated. These results were correlated with arthroscopic findings and analysed statistically. With arthroscopic findings used as the standard of reference, the sensitivity and specificity of 10%, 11% and 12% extrusion thresholds, and 3 mm of medial meniscal extrusion (MME) as diagnostic thresholds, were calculated. RESULTS: The mean length of the meniscal extrusions of meniscal root tears was twice as long as the control group. The mean L/T ratio of the meniscal root tears was approximately 13%, while those of the control groups were 5%. The differences in the L and L/T between the meniscal root tears and normal and meniscal root tears and other meniscal tears were statistically significant (p<0.001), but those between normal and other meniscal tears were not. The best diagnostic discrimination was achieved using an extrusion ratio threshold of 10% (79% sensitivity, 86% specificity). The 3 mm of MME threshold demonstrated high specificity (98%), but not high sensitivity (54%). CONCLUSION: The mean L/T ratio of the meniscal root tears was approximately 13% and was statistically significant. The best diagnostic discrimination was achieved using an extrusion ratio threshold of 10%. ADVANCES IN KNOWLEDGE: The use of the L/T ratio in combination with MME can be a useful method for evaluating medial meniscal root tears.